Knjiga obračunov celjskih mestnih sodnikov (1457-1513) - Bizjak, Matjaž (ZRC SAZU, Založba ZRC, 2010)
On 9 November 1456, Ulrich II, the last Count of Celje, was murdered in Belgrade. Not long afterwards, Celje fell under the rule of the Habsburg Emperor Frederick III, who set the new foundations for the city's autonomy. The account book of the city judges of Celje, which is kept in the Styrian Provincial Archives in Graz - the oldest source of this kind from the territory of the present-day Slovenia - documents in detail the first fifty years of operations and transactions conducted by the new city authorities and brings an abundance of interesting features from the late medieval urban daily life. The source is published in its original language and parallel Slovenian translation, with an added scholarly introduction that provides the reader with an insight into Celje's self-administration, development and medieval accounting systems, as well as presents the manuscript of the published source, together with the measuring and monetary systems used therein.